Analisis Psikologis Strategi Pemasaran Digital Dalam Industri Musik: Studi Kasus pada Lagu Bunga Hati – Salma Salsabil Idol 12 - Syafrida, Alyazra (Brand Communication, 2024)
This research aims to conduct a psychological analysis of digital marketing strategies employed in the music industry, focusing on the song "Bunga Hati" performed by Salma Salsabil, a contestant in the 12th season of Indonesian Idol. Through a case study approach, we explore how elements of digital marketing such as visuals, narratives, and fan interactions can influence consumer perceptions and psychological responses. The research methodology includes sentiment analysis of online responses to the song, visual interpretation of digital marketing materials, and understanding direct interactions between Salma Salsabil and her fans on digital platforms. Research findings indicate that digital marketing strategies that build emotional connections with the audience have a positive impact on perceptions of the song and the artist. The discussion involves interpreting findings within the context of consumer psychology theories and the success of digital marketing strategies in creating a deeper experience for listeners. The implications of this research can offer valuable insights for marketing practitioners in the music industry to understand how the use of digital marketing strategies can create deeper psychological effects on the audience, particularly in the context of competitions like Indonesian Idol. The conclusion of this research highlights the importance of integrating psychological elements in the development of digital marketing strategies in the music industry, providing a foundation for further research in this field.